2018
DOI: 10.5946/ce.2017.123
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Retrograde Cholangiopancreatography in Nonagenarian Patients: Is It Really Safe?

Abstract: Background/AimsLiterature on the safety of endoscopic retrograde cholangiopancreatography (ERCP) in elderly patients is divided. Based on this we decided to examine the safety of ERCP in nonagenarian patients.MethodsA total of 1,389 patients, with a mean age of 63.94±19.62 years, underwent ERCP during the study period. There were 74 patients aged 90 years or older with a mean age of 92.07±1.8. Logistic regression showed that nonagenarian patients had a significantly increased odds of in-patient mortality (adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…[13][14][15][16][17] In the present study, the adverse event rate was 11% (8/73). Although elderly patients have multiple diseases and functional disorders, ERCP appears to be a safe and effective method even in very old patients.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…[13][14][15][16][17] In the present study, the adverse event rate was 11% (8/73). Although elderly patients have multiple diseases and functional disorders, ERCP appears to be a safe and effective method even in very old patients.…”
Section: Discussionsupporting
confidence: 44%
“…Zain et al 17 reported an all-cause inpatient mortality rate of 12.2%, and Mitchell et al 18 reported an all-cause inpatient mortality rate of 13%. No other study has reported long-term OS after ERCP in nonagenarian patients, although a few studies mentioned the mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Further, although several studies have reported that ERCP was safe in patients aged ≥90 years, the control groups in several of them included younger patients. [10][11][12] In a recent retrospective study, the ERCP mortality rate increased in the super-old (those aged ≥90 years), but the AE occurrence rate was not significantly different compared with those aged <90 years 13 . We aimed to identify factors contributing to AE in ERCP in patients aged ≥85 years and to examine whether ERCP is safe in the super-old.…”
Section: Introductionmentioning
confidence: 99%
“…Complications have been observed during the early postoperative period in 1.6% of patients older than 90 years [ 2 , 3 ]. In a retrospective single-center study conducted by Sobani et al [ 4 ] performed with 1389 patients, 74 patients were ≥90 years of age, and the success rate of ERCP was 89.2%. The authors emphasized the safety of this procedure, even in this age group, provided that the necessary preparation is performed.…”
mentioning
confidence: 99%